I. The Enantioselective Synthesis of Chiral Allenyl Carbonyl Compounds and Their Use as Synthetic Intermediates II. Rhodium-Catalyzed C-H Functionalization: Application to the Synthesis of 3-Carboxylindoles and Attempted Applications to Allenes - Shore, Daniel Gordon Michael (Université d'Ottawa / University of Ottawa, 2011)
Allenes are unique compounds in organic chemistry by virtue of their adjacent, orthogonal π-bonds. While of limited use in and of themselves, some classes of allenes have found use in organic synthesis as building blocks for more complex products. Previous work in the Fagnou group has identified a silver lewis acid-catalyzed enantioselective isomerization protocol for the synthesis of allenyl esters and amides. This protocol has been subject to reproducibility issues, the source of which is explored in this thesis. Initial work into the development of a phase-transfer catalytic process for the isomerization of alkynyl amides is also presented. The use of allenyl esters in lactonization reactions has become more common in recent years. The scope of the halolactonization of allenyl esters to form halobutenolides is explored here. The lactonization of allenyl carboxylic acids has also been demonstrated in the literature. The attempted synthesis of allenyl carboxylic acids via the oxidative deprotection of dimethoxybenzyl esters is also presented. Indole is an important and biologically and medicinally relevant compound in organic synthesis. Though many classical methods for its synthesis exist, the discovery of new, complex indole-containing compounds necessitates the development of efficient ways to synthesize indoles. Previous work in the Fagnou group has led to the discovery of a rhodium-catalyzed oxidative synthesis of indole with a key C-H functionalization step. This protocol has been applied to alkynyl esters to synthesize an array of 3-carboxylindoles in moderate to good yields. The competency of allenes as an intra- and intermolecular coupling partner in a similar rhodium-catalyzed hydroarylation reaction has also been explored, leading to the discovery that allenyl compounds are not tolerated in this reaction protocol.
Keywords: Allene; Rhodium